Robbing Peter to Pay Paul? The Redistribution of Wealth Caused by Rent Control - Ahern, Kenneth R.,Giacoletti, Marco (National Bureau of Economic Research, 2022)
We use the price effects caused by the passage of rent control in St. Paul, Minnesota in 2021, to study the transfer of wealth across income groups. First, we find that rent control caused property values to fall by 6-7%, for an aggregate loss of 1.6 billion. A calibrated model of house prices under rent control attributes a third of these losses to indirect, negative externalities. Second, leveraging administrative parcel-level data, we find that the tenants who gained the most from rent control had higher incomes and were more likely to be white, while the owners who lost the most had lower incomes and were more likely to be minorities. For properties with high-income owners and low-income tenants, the transfer of wealth was close to zero. Thus, to the extent that rent control is intended to transfer wealth from high-income to low-income households, the realized impact of the law was the opposite of its intention
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Verteilungswirkung; Mietenpolitik; USA; Allocative Efficiency; Cost– Benefit Analysis; Externalities; Household Saving; Borrowing; Debt; and Wealth; Externalities; Redistributive Effects; Environmental Taxes and Subsidies; Regional Migration; Regional Labor Markets; Population; Neighborhood Characteristics; Housing Supply and Markets; Other Spatial Production and Pricing Analysis; Government Policy